Chromosome-scale assembly of Artemia tibetiana genome, first aquatic invertebrate genome from Tibet Plateau - Panpan Chen; Zhaoyan Zhong; Wei-Xin Jin; Jin Sun; Shi-Chun Sun (Scientific Data)
Abstract Genomic-level studies on the adaptive evolution of animals in the Qinghai-Tibet Plateau have been rapidly increasing. However, most studies are concentrated on vertebrates, and there are few reports on invertebrates. Here, we report the chromosome-level genome assembly for the brine shrimp Artemia tibetiana from Kyêbxang Co, a high-altitude (4620 m above sea level) salt lake on the plateau, based on the combination of Illumina, Nanopore long-reads and Hi-C sequencing data. The assembled genome is 1.69 Gb, and 94.83% of the assembled sequences are anchored to 21 pseudo-chromosomes. Approximately 75% of the genome was identified as repetitive sequences, which is higher than most crustaceans documented so far. A total of 17,988 protein-coding genes were identified, among them 14,388 were functionally annotated. This genomic resource provides the foundation for whole-genome level investigation on the genetic adaptation of Artemia to the harsh conditions in the Qinghai-Tibet Plateau.